Pancreatic hamartoma: detection of harbouring NAB2:STAT6 fusion gene. Issue 3 (14th July 2022) - Tanigawa, Masahiko; Koga, Yutaka; Naito, Yoshiki; Yamaguchi, Hiroshi; Iwasaki, Takeshi; Kohashi, Kenichi; Ohike, Nobuyuki; Hanada, Keiji; Higashi, Michiyo; Komatsu, Masato; Imai, Hiroshi; Yamakita, Keisuke; et al.
Aim: Hamartomas in the pancreas are rare and are often histologically and morphologically similar to solitary fibrous tumours (SFTs). We examined the differences between hamartomas and SFTs at the molecular level. Methods and results: Thirteen patients histopathologically diagnosed with pancreatic hamartoma were included in the study. We also performed STAT6 immunohistochemistry (IHC), which is used in the diagnosis of SFT. Furthermore, for the three cases in which RNA was extracted, reverse transcription polymerase chain reaction to search for NAB2::STAT6 fusions was used. Macroscopically, 13 patients had well‐demarcated tumour lesions. Histologically, no islets of Langerhans were observed in the lesions, acinar tissue and ducts were unevenly distributed and elastic fibres were not observed around the ducts by Elastica van Gieson staining. One case contained a lipomatous hamartoma composed mainly of adipose tissue. Seven of the 13 cases demonstrated expression of STAT6 in the nuclei of intervening spindle cells. NAB2::STAT6 fusions were observed in two of the three cases in which RNA was extracted. These two cases also demonstrated STAT6 expression in spindle cells using STAT6 IHC. In one case of lipomatous hamartoma, we did not confirm NAB2::STAT6 fusion or STAT6 expression in STAT6 IHC. Conclusion: Of the 13 patients histopathologically diagnosed with hamartoma, two demonstrated NAB2::STAT6 fusions, suggesting the existence of pancreatic hamartomas with molecular‐level components identical to those of SFT. Abstract : The nuclei of spindle cells inside the lesion are positive for STAT6 staning. A NAB2::STAT6 fusion gene is detected, and fusion between the NAB2 and STAT6 genes is also comfirmed by fusion gene sequencing.